KATEKESE KONTEKSTUAL: SARANA DALAM MEMBANGUN GEREJA SEBAGAI UMAT ALLAH DI PAROKI ST. HILARIUS KLEPU - Stevanus Danang Setiyono; Agustinus Supriyadi (Lembaga Penelitian STKIP Widya Yuwana, 2019)
Catechesis appropriate to the situation and needs of the people is known as contextual catechesis. Catechesis of contextual context emphasizes the people